MEDICAL PROBLEM, CONCEQUENCES TO ORAL CARE IN GERIATRIC PATIENT - Nadia Hardini; Oedijani Santoso (Jurnal Kedokteran Diponegoro)
Introduction: Oral and maxillofacial tissue status has a significant impact on the systemic health of elderly patients. Elderly patients without oral diseases are rare to find by dentists. Literature Review: Prevention and treatment for caries and periodontal diseases should be done for elderly patients, except in particular conditions when its not worth the risks treatments. Although the relationship between oral diseases and systemic diseases is still controversial and unresolved, it can be assumed that elderly patients have a greater risk of acute and chronic oral infections due to the use of various drugs and medical disorders, impaired immune function, age related impaired kidney, liver and cardiovascular dysfunction. Conclusion: While on duty, dentists who provides care to elderly patients, must know the medical history and systemic review, and understands general medical problems that affects oral care of the elderly.